ANALYSIS THERMAL STORAGE TEMPERATURE CONTROL FOR SOLAR THERMAL POWER PLANT - Handy Dewanto, Fauzi
Utilization of new and renewable energy sources is currently one of Indonesia's intensified agendas, one of which is in the power generation sector. An emerging alternative is the use of solar energy as renewable energy. However, the problem of intermetance in solar energy is a minus value compared to fossil fuel plants. The technology of concentrating problem power is one of the solutions for the utilization of solar energy with thermal storage. For the operation of concentrating solar power as baseload, a special control system is required. This research focuses on developing control systems for baseload generation for thermal solar power plants. The analysis in this study shows that the temperature control in the CSP system with storage can produce baseload 50 MW power generation for the Rankine cycle and the sCO2 cycle.